SWEETNESS LEVELS AND EFFECTS ON CATA SENSORY PROFILE AND ACCEPTANCE OF PEACH NECTAR - Silva, Marselle Marmo do Nascimento; Menezes, Leonardo Moreira; de Queiroz, Alisson Ferreira; Melo, Lauro (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2016)
Fruit nectars are beverages consisting of important nutrients, with a good extension of shelf life and are well accepted by consumers. Aiming to further enhance their positive characteristics, this study aimed to discuss the reduction of the sugar content present in peach nectar from the sensory analysis of commercial samples. Ranking, acceptance, just-about-right scale and check-all-that-apply (CATA) tests were performed, allowing to observe the effect of different sensory attributes on acceptance of nectars and to define the ideal sugar content. It was possible to found that some commercial samples did not present the ideal sweetness and that the sweetness is not the main attribute on the acceptance of peach nectar, demonstrating the complexity of its food matrix. This complexity seemed to divide consumer preference and it was possible to identify groups that differ regarding the acceptance of the samples. The sample A has always been in the group of the most accepted samples and, depending on the attribute, it did not differ significantly from the other samples (p>0.05). The ideal sweetness sample was less accepted due to the strong influence of herbal flavor and herbal aroma in the pulp used in its preparation.